Crime in the dark: Role of electricity rationing - Imelda; Xiaoying Guo (Graduate Institute of International and Development Studies, 2024)
In many developing and emerging economies, frequent power outages are often a consequence of electricity rationing, stemming from the insufficient generation capacity to meet peak demand. In an effort to minimize the disruption caused by sudden power outages, utilities often implement scheduled outages to allow consumers to prepare. However, these planned outages may inadvertently influence criminal behavior and planning. This study investigates the causal relationship between planned electricity outages and crime rates, leveraging a geographic discontinuity in outage duration due to differences in electricity suppliers within the City of Cape Town, South Africa. We compare crime trends in areas served by the municipal grid, which benefits from pumped hydro storage to mitigate outages, with those served by the national grid, where outages are more severe. We find that 10 hours per month more outages lead to an increase of 2.6 percent or eight more crime incidents. The analysis reveals that while overall crime rates are affected, specific types of crime, such as robbery, theft, and violent crime, are particularly sensitive to power outages. Outages caused by electricity rationing create opportunities for certain types of criminal activity, particularly at night. The larger the share of areas affected by severe load shedding, the higher the incidence of crime. Conversely, crimes less related to load shedding, such as commercial and drug-related offenses, are not affected by these outages.This research contributes to the growing body of evidence on the socioeconomic consequences of power outages and highlights the importance of reliable electricity access for public safety and development.
Keywords: O18; O17; K42; 330; outages; developing countries; crime; law enforcement